(untitled) (Current Horticulture, 2024)
Twenty six rose (Rosa × hybrida L.) cultivars grown for open field conditions were characterized using 16 vegetative and floral traits to obtain information on the nature and magnitude of existing genetic variability. The cultivars, Night Time, Christian Dior and Pusa Abhishek were early in flowering and Local Collection 3, Local Collection 4, Kashmir Velvet and Edouard had longer flowering duration; Christian Dior and Bonne Nuit had bigger flowers; Pusa Bahadur had long flower stalk; Local Collection 3, Local Collection 4, Edouard and Kashmir Velvet were having more number of flowers per plant and Pusa Bahadur, Night Time and Christian Dior were found with higher flower weight and shall help in further selection and hybridisation. The higher genotypic and phenotypic coefficients of variation were recorded for plant height, plant spread (E-W), plant spread (N-S), stem girth, number of shoots/ plant, number of petals/ flower, flower stalk length, number of flowers/ plant and 100-flower weight, indicating that genotypic variation contributed markedly towards total variability for the above traits. There is a greater scope for selection in improving flower yield. The high heritability with high expected genetic advance over mean (GAM) was observed for plant height, plant spread (E-W), plant spread (N-S), stem girth, number of shoots/ plant, flower bud length, flower diameter and flower stalk length. This also revealed the lesser influence of environment on these traits. Therefore, simple selection based on phenotypic values for these traits could be useful in their improvement for achieving higher flower yield. The trait specification identified genotypes could ideally be used as donor parents in rose breeding programme to develop desired genotypes for open field cultivation.